Beyond to the Stable: Role of the Insertion Sequences as Epidemiological Descriptors in Corynebacterium striatum - Leyton-Carcaman, Benjamín; Abanto, Michel (Frontiers in Microbiology, 2022)
In recent years, epidemiological studies of infectious agents have focused mainly on the pathogen and stable components of its genome. The use of these stable components makes it possible to know the evolutionary or epidemiological relationships of the isolates of a particular pathogen. Under this approach, focused on the pathogen, the identification of resistance genes is a complementary stage of a bacterial characterization process or an appendix of its epidemiological characterization, neglecting its genetic components’ acquisition or dispersal mechanisms. Today we know that a large part of antibiotic resistance is associated with mobile elements. Corynebacterium striatum, a bacterium from the normal skin microbiota, is also an opportunistic pathogen. In recent years, reports of infections and nosocomial outbreaks caused by antimicrobial multidrug-resistant C. striatum strains have been increasing worldwide. Despite the different existing mobile genomic elements, there is evidence that acquired resistance genes are coupled to insertion sequences in C. striatum. This perspective article reviews the insertion sequences linked to resistance genes, their relationship to evolutionary lineages, epidemiological characteristics, and the niches the strains inhabit. Finally, we evaluate the potential of the insertion sequences for their application as a descriptor of epidemiological scenarios, allowing us to anticipate the emergence of multidrug-resistant lineages.